2013
DOI: 10.1088/2043-6262/4/2/025003
|View full text |Cite
|
Sign up to set email alerts
|

Quick synthesis of highly aligned or randomly oriented nanofibrous structures composed of C 60 molecules via self-assembly

Abstract: Assemblies, which are composed of nanoparticles such as nanofibres, have been intensively studied in recent years. This has particularly been the case in the field of biomedicine, where the aim is to develop efficient methodologies for capturing and separating target biomolecules and cells and/or encouraging bio-chemical reactions, utilizing the extremely high surface area to volume ratio of assemblies. There is an urgent need for the development of a quick synthesis method of forming nanofibrous structures on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…100 μL of the solution of C 60 and sulphur dissolved in benzene was dropped onto the glass substrate, the temperature of which had been set at 75 °C, as mentioned, and we found that fibres were formed by C 60 and sulphur after the evaporation of benzene. Note that no fibres were grown without sulphur [ 40 , 41 ] and therefore it is supposed that mixing sulphur and C 60 with the solvent is essential for the formation of fibres [33] . SEM images and EDS mappings of the fibres are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…100 μL of the solution of C 60 and sulphur dissolved in benzene was dropped onto the glass substrate, the temperature of which had been set at 75 °C, as mentioned, and we found that fibres were formed by C 60 and sulphur after the evaporation of benzene. Note that no fibres were grown without sulphur [ 40 , 41 ] and therefore it is supposed that mixing sulphur and C 60 with the solvent is essential for the formation of fibres [33] . SEM images and EDS mappings of the fibres are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The length and width of each fibre were, respectively, of the order of 10 μm and 100 nm. In our previous study, in which case the concentration of C 60 molecules and sulphur was set at 0.6 and 3.1 μmol mL −1 and the surface temperature of the substrate was lower than 50 °C, highly aligned C 60 fullerene nano fibres were grown in perpendicular directions along the circumference of a droplet via the coffee ring effect [33] , noting that no fibres were formed in the central part of the substrate. In the present study, on the contrary, fibres were synthesised in the droplet during the evaporation process and finally deposited evenly on the surface of the substrate due to the relatively high concentration of C 60 molecules and sulphur; 1.2 and 6.2 μmol mL −1 , and high evaporation rate; i.e., the substrate temperature was set at 75 °C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Due to their marvellous potential application in many areas, several methods have been developed for the construction of FNFs. They are (1) solution evaporation, 10,11 (2) template techniques, 12,13 (3) surfactant-assisted methods, 14 volatile diffusion method, 15 and (4) LLIP method. 16,17 With the advantages of no requirement of physical templates and catalysts, the LLIP method is generally acknowledged as a way of great promise for self-assembly of this 1D structure.…”
Section: Introductionmentioning
confidence: 99%